SPEECH SCRAMBLING BASED ON CHAOTIC MAPPING AND RANDOM PERMUTATION FOR MODERN MOBILE COMMUNICATION SYSTEMS - G, Dhanya; Jayakumari, J (APTIKOM Publisher, 2017)
The expanding significance of securing data over the network has promoted growth of strong encryptionalgorithms. To enhance the information protection in network communications, this paper presents a Randompermutation, chaotic mapping and pseudo random binary scrambling. It involves transforming the intelligible speechsignal into an unintelligible form to protect it from interrupters. In this report, suggest a simple and secure procedureto secure the speech signal. The speech scrambling process makes use of two Permutations. In the first step, Randompermutation algorithm is used to swap the rows of the original speech followed by swapping of rows using chaoticBernoulli mapping. This produces an intermediary scrambled speech. In the second measure, pseudo random binarygenerator is used to make the final scrambled signal. Various analysis tests are then executed to determine thequality of the encrypted image. The test results determine the efficiency of the proposed speech scrambling process.